Clinico-haematological profiling of transfusion dependent and non transfucion dependent beta thalassaemia syndrome in Kedah - Azizi, Fahmaa (2020)
Introduction: β thalassaemia is a group of haemoglobin diseases caused by a reduction or absence in the synthesis of β globin chains. Affected individuals can be heterozygous, compound heterozygous, or homozygous for β thalassaemia, or even have interactions with other haemoglobinopathies. Kedah has a high prevalence of thalassaemia patients with 20.25/100000 populations. Different mutations have been identified in the β globin (HBB) gene generating diverse clinical phenotypes in β thalassaemia. The identification of the genotype is important for proper counselling to patients and their families. Objectives: To determine the clinical, haematology and β mutation profiling of β thalassaemia patients in Kedah. Methods: 100 patients with β thalassaemia were traced through hospital information system. A detailed clinical and laboratory records of patients were retrieved. For β thalassaemia genotyping, 20 different mutations were tested by MARMS technique. Result and Discussions: Out of 100 patients, 66% were transfusion dependent (TDT) and 34% of the studied patients were non transfusion dependent (NTDT). In this study the TDT patients had significantly lower mean age of diagnosis with 2.75 (2.28) years as compared to 19.87(17.87) years in NTDT (p <0.001). There was statistically significant presence of short stature and a larger mean size of spleen in patients with TDT as compared to NTDT. The significant differences between haematological parameters in both groups of patient were well observed in this study. Both NTDT and TDT group of patients were among compound heterozygous Hb E/ β thalassaemia with 85.3% and 75.8% respectively. In TDT patients, the commonest mutations observed was CD26(G>A)/IVS1-5(G>C) (28.8%), followed with CD26(G>A)/IVS1-1(G>T) (13.6%) and CD26(G>A)/CD41/42(-TTCT) (13.6%). In the NTDT group, the common mutations observed were IVS1-1(G>T) and CD19 trans to Hb E (CD26 (G>A) with 32.4% and 29.4%, respectively. It was noted in this study, diversity of phenotypes in patients with mutation CD26(G>A)/IVS1-1(G>T), thus indicating other genetic modifiers to be explored in these patients. An increment of 1 % of Hb A level at diagnosis have reduced odds of transfusion dependency by 7% (adjusted OR 0.93,95% CI: 0.90, 0.97; p<0.001) when adjusted for Hb F. Whereas, an increase in 1% of Hb F level, had 1.04 times higher odds to be transfusion dependent (adjusted OR 1.04,95% CI: 1.01, 1.07, p = 0.007) when adjusted for Hb A level. Conclusion: There are diversity of type of β mutation. haematological and clinical parameters among β thalassaemia patients in Kedah.